2022
DOI: 10.3390/s22083014
|View full text |Cite
|
Sign up to set email alerts
|

Retention Effects of Long-Term Balance Training with Vibrotactile Sensory Augmentation in Healthy Older Adults

Abstract: Vibrotactile sensory augmentation (SA) decreases postural sway during real-time use; however, limited studies have investigated the long-term effects of training with SA. This study assessed the retention effects of long-term balance training with and without vibrotactile SA among community-dwelling healthy older adults, and explored brain-related changes due to training with SA. Sixteen participants were randomly assigned to the experimental group (EG) or control group (CG), and trained in their homes for eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…However, they will regularly experience hundreds of specific balance stimuli/hour that are intimately integrated into their regular standing and walking activities and that are likely to cause related changes in balance behavior. Over time, this feedback may lead to a reweighting of sensory information that is relevant for balance function ( Sienko et al, 2018 ), as has previously been suggested in older adults performing in-home balance training using vibrotactile sensory stimulation related to trunk tilt ( Noohi et al, 2017 , Bao et al, 2018 ) further supported by recently reported changes in brain connectivity ( Bao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 71%
“…However, they will regularly experience hundreds of specific balance stimuli/hour that are intimately integrated into their regular standing and walking activities and that are likely to cause related changes in balance behavior. Over time, this feedback may lead to a reweighting of sensory information that is relevant for balance function ( Sienko et al, 2018 ), as has previously been suggested in older adults performing in-home balance training using vibrotactile sensory stimulation related to trunk tilt ( Noohi et al, 2017 , Bao et al, 2018 ) further supported by recently reported changes in brain connectivity ( Bao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 71%
“…However, they will regularly experience hundreds of specific balance stimuli/hour that are intimately integrated into their regular standing and walking activities and that are likely to cause related changes in balance behavior. Over time, this feedback may lead to a reweighting of sensory information that is relevant for balance function (Sienko, Seidler et al 2018), as has previously been suggested in older adults performing in-home balance training using vibrotactile sensory stimulation related to trunk tilt (Noohi, Kinnaird et al 2017, Bao, Carender et al 2018) further supported by recently reported changes in brain connectivity (Bao, Noohi et al 2022).…”
Section: Discussionmentioning
confidence: 71%
“…However, they will regularly experience hundreds of specific balance stimuli/hour that are intimately integrated into their regular standing and walking activities and that are likely to cause related changes in balance behavior. Over time, this feedback may lead to a reweighting of sensory information that is relevant for balance function (Sienko, Seidler et al 2018), as has previously been suggested in older adults performing in-home balance training using vibrotactile sensory stimulation related to trunk tilt (Noohi, Kinnaird et al 2017, Bao, Carender et al 2018) further supported by recently reported changes in brain connectivity (Bao, Noohi et al 2022). Interestingly, early observations from a pilot study of five participants in the cohort studied here, who completed 26 weeks of device use, show neuroplastic changes in brain network connectivity related to postural control and balance that were associated with improved changes in FGA scores (Hsu, Iloputaife et al 2021).…”
Section: Exercise Dosing Versus Daily Exposure From Sensory Prosthesi...mentioning
confidence: 70%
“…Among the included studies, exergaming with balance platforms 20 – 41 ( n = 22, total participants: 1084) and motion capture 42 – 58 ( n = 17, total participants: 912) were the most frequently investigated interventions. Seven studies (total participants: 452) examined the use of other serious games 59 65 , four studies (total participants: 98) examined interventions with wearables 66 69 , and three studies (participants: 619) investigated telerehabilitation 70 72 . Two studies could not be classified into either group as it involved an intervention with the Nintendo Switch console 73 , 74 .…”
Section: Resultsmentioning
confidence: 99%